Selectivity of Incilius valliceps (Anura: Bufonidae) tadpoles on freshwater zooplankton - Joan Jacobson, Brianna; Cervantes-Martínez, Adrián; Gutiérrez-Aguirre, Martha Angélica (HIDROBIOLÓGICA, 2017)
The dietary preferences of tropical tadpoles and the way they interact with zooplankton often go unstudied in aquatic ecosystems. Goals. We investigated the interactions between Incilius valliceps tadpoles and a freshwater zooplankton community found in an artificial aquatic pond located on Cozumel Island in Quintana Roo, Mexico. Methods. We determined zooplankton abundance, richness, the Shannon-Wiener diversity index, and the proportion of each zooplankton species in the environment. We also evaluated characteristics of the tadpole population such as body size, abundance, and proportion of prey ingested as determined by stomach content analysis. We used the Jacobs selectivity index to determine tadpole prey of preference. Results. The rotifers Anuraeopsis fissa and an unidentified species of Bdelloidea group were dominant among the eight zooplankton species consumed. The selectivity index showed that I. valliceps tadpoles preferred to consume macro-zooplankton (ostracods and cladocerans) instead of the rotifer species available. Tadpoles positively chose Cypridopsis vidua throughout their growth and development and Moina wierzejskii during their early developmental stages, and negatively selected the rotifer species of the one unidentified species of Bdelloidea, A. fissa, and Epiphanes brachionus. In the presence of tadpoles, Keratella americana, Lepadella patella, and Lecane luna were either present in extremely low abundances or not found in the aquatic community, and M. wierzejskii produced males and resistant eggs. Conclusions. The findings of this study clarify the dietary needs of tropical tadpoles and their role in aquatic ecosystems.